Répression et résurgence du judaïsme dans Daniel Deronda : les voies de la masculinité sont-elles impénétrables ? - Gilbert Pham-Thanh (Cahiers Victoriens et Edouardiens)
George Eliot’s Daniel Deronda constitutes an inspiring testimony to 19th-century patriarchal society. It explores the fault lines of the British androcentric system through the diegetic itinerary of its eponymous hero and his compatriots, who cut unremarkable figures of respectability. The text goes on to fathom the alternative openings that resurgent Judaism offers to rejuvenate the dominant males of the Christian community. Indeed, it is when the hero learns about his true Jewish identity that all the scattered elements of his literary existence fall into place — he now unerringly senses that he must embark on a Zionist expedition to the East after marrying Mirah, a Jewess he met. More surprisingly, in a text that still pays homage to male supremacy, some remarkable reformulations of masculinity tend to reorient the discourse on gender and allow for a relative blurring of the line of divide between the sexes, which still leaves the ways of masculinity quite impenetrable.